(untitled) (Fiep Bulletin - online, 2012)
The text aims to evidence the different questions that involved development of the Human Kinetics, fromits origin of a new Science, proposed by the Portuguese Philosopher Manuel Sergio Vieira and Cunha, pointingout its importance and significance for the Physical Education area, once we consider that this was a theory thatsupported the implantation of the Physical Education University Courses in Brazil, bringing up severaldiscussions about the object of study that must sustain this knowledge area, starting up a debate in differentSpecialists Commissions, which write the justifications that based the resolutions from the National EducationDepartment, and the Ministry of Education, and which were used to establish the parameters of the NationalCurricular Guidelines for the formation of professionals of this knowledge area. In this text, it’s explicit that theHuman Kinetics does not represent only a simple change of name, because it announces a new Science thatstudies the intentional, spontaneous, free and disinterested human movement, which allows the transcendence,and, therefore, brings out all the moments of the human being life, from the birth until the death, favoring that thesport, the dance, the ergonomics, the fights, the rehabilitation, the yoga, are based on it, becoming, with allrelevancy, the scientific root of the various aspects of the human kinetics.